PENGARUH IKATAN KEPENTINGAN KEUANGAN, FEE AUDIT, SIFAT MACHIAVELLIAN, DAN PEMAHAMAN ETIKA PADA INDEPENDENSI PENAMPILAN AUDITOR - Saputra, I Gede Agus Angga; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 16 No 1 (2016), 2016)
This research discusses abaout effect of interest rate, exchange rate, leverage and profitability in stock returns. Stock returns in this research is the level of benefits of owning a stock investor on investments made in the property company to go public in Indonesia Stock Exchange. This type of research used in this study is exploratory research. This research requires date that originates on the Stock Exchangend. Based on the results of regression analysis found that the level of interest rates, the exchange rate negative effect stock returns on property companies which go public in Indonesia Stock Exchange, leverage and profitability positive effects stock returns on property companies which go public in Indonesia Stock Exchange
Keywords: Interest Rate, Leverage,and Profitability